Self confidence in a sample of students of the Faculty of Education, Tishreen University A field study - Sbeira, Fouad (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of the study was to reveal the existence of self-confidence in a sample of students of the Faculty of Education at Tishreen University, and to detect the differences between males and females, and differences according to the secondary certificate (literary-scientific) and the place of residence (rural-city) From the College of Education. The descriptive method was used and was based on the Sidney Shrauger scale prepared by Abdullah (1997). The research found the following results: There is self confidence in the research sample, and there are no statistically significant differences depending on the variables (gender, specialty, place of residence). The study suggests increasing attention to positive personality variables that will support the positive aspects of personality and achieve healthy psychosocial development, and support the success and academic achievement of students at all levels of study.